2018
DOI: 10.1186/s12959-018-0166-4
|View full text |Cite
|
Sign up to set email alerts
|

Association between plasminogen activator inhibitor-1 and cardiovascular events: a systematic review and meta-analysis

Abstract: BackgroundSmall studies have implicated plasminogen activator inhibitor-1 (PAI-1) as a predictor of cardiovascular events; however, these findings have been inconsistent.We sought out to examine the potential role of PAI-1 as a marker for major adverse cardiovascular events (MACE).MethodsWe systematically reviewed all indexed studies examining the association between PAI-1 and MACE (defined as death, myocardial infarction, or cerebrovascular accident) or restenosis. EMBASE, Web of Science, Medline, and the Coc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
54
0
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(81 citation statements)
references
References 78 publications
6
54
0
6
Order By: Relevance
“…Research of Tani et al (2015) in DM2 patients indicated significant decreased PAI-1 level, serum TGL, and Apo B concentration after vildagliptin treatment [29]. A systemic review of 38 articles evaluating PAI-1 levels in 11,557 patients revealed that elevated plasma PAI-1 antigen levels are associated with higher risk of death, myocardial infarction, or cerebrovascular accident [108].…”
Section: Lipids Metabolism Disordersmentioning
confidence: 99%
“…Research of Tani et al (2015) in DM2 patients indicated significant decreased PAI-1 level, serum TGL, and Apo B concentration after vildagliptin treatment [29]. A systemic review of 38 articles evaluating PAI-1 levels in 11,557 patients revealed that elevated plasma PAI-1 antigen levels are associated with higher risk of death, myocardial infarction, or cerebrovascular accident [108].…”
Section: Lipids Metabolism Disordersmentioning
confidence: 99%
“…Chemerin, is a chemoattractant protein, that is necessary for adipogenesis, which when elevated in adipose tissue may be a marker for the onset of DM [17]. Visfatin is an enzyme that activates insulin and has insulin-mimetic effects [18], whereas plasminogen activator inhibitor-1 (PAI-1), is the primary inhibitor of tissue-and urokinase-type plasminogen activators, and considered to be a critical regulator of the fibrinolytic system [19]. Finally, resistin promotes hepatic production of low density lipoproteins (LDL), which degrades LDL receptors [20].…”
Section: Introductionmentioning
confidence: 99%
“…Stress has a great impact on neurodegenerative diseases, having a great role in its development, progress and evolution [180]. [188].…”
Section: Metabolic Diseases and Their Affinity For Alzheimer's Diseasementioning
confidence: 99%